Mites of the genus Typhlodromus (Acari: Phytoseiidae) from Southern France: combined morphological and molecular approaches for species identification - Tixier, Marie-Stéphane; Dennj, Principato; Douin, Martial; Kreiter, Serge; Haralabos, Tsolakis (Zootaxa, 2019)
Mites of the family Phytoseiidae are important predators for biological control applications. They occur naturally in ecosystems but their overall distribution is not completely known. This study presents results of surveys carried out in the south of France. It proposes the use of a combination of morphological and molecular approaches for species diagnosis. Eighteen species of the genus Typhlodromus are reported from southern France, of which nine belong to Typhlodromus (Anthoseius) and nine to Typhlodromus (Typhlodromus). Eight of these species are new to the French fauna. The mitochondrial DNA CytB gene from 85 specimens (18 species) and the 12S rRNA gene from 30 specimens (9 species) were partially sequenced and analysed. Based on molecular and morphological comparisons, the synonymy between Typhlodromus (Anthoseius) ilicis and T. (A.) creticus is discussed. High genetic distances between specimens morphologically assigned to T. (A.) rhenanoides suggests the existence of cryptic species. The reliability of integrative approaches for species identification is discussed.